Growth-inhibiting effects of taxol on human liver cancer in vitro and in nude mice - Yuan, Jin Hui (World J Gastroenterol, 2000)
AIM: To investigate the effects of taxol on SMMC-7721 human hepatoma and its mechanisms. METHODS: In vitro cell growth was assessed by trypan blue exclusion method. Experimental hepatoma model was established by seeding SMMC-7721 cells subcutaneously into Balb/c (nu/nu) nude mice. In vivo tumor growth was determined by measurement of tumor diameter with Vernier calipers. The syntheses of DNA, RNA and protein were analyzed by incorporation of (3)H-thymidine, (3)H-uridine and (3)H-leucine respectively. Using light and electron microscopes to observe the morphological changes of cells including mitosis and apoptosis. RESULTS: Taxol was effective against SMMC-7721 human hepatoma cell growth in the ranges of 2.5 nmol/L-10 nmol/L- with mitotic arrest and apoptosis in vitro. DNA, RNA and protein syntheses in cells were also obviously suppressed by in vitro treatment of taxol for 72 h. Taxol at 2.5 nmol/L reduced (3)H-thymidine uptake to about 34% of the control value (P ＜ 0.05). Increasing the dose of taxol to 20 nmol/L resulted in a greater decrease in (3)H-thymidine incorporation to 60% of the control value (P ＜ 0.01). At a concentration of 20 nmol/L, the (3)H-uridine and (3)H-leucine uptakes were reduced to 52% (P ＜ 0.05) and 63% (P ＜ 0.01), respectively. In vivo, taxol significantly inhibited SMMC-7721 tumor growth at 10 mg/kg, i.p. once daily for 10 d. A more than 90% decrease in tumor volume was observed by day 11 (P ＜ 0.01) similarly with mitotic arrest and cell apoptosis. CONCLUSION: Taxol has a marked anticancer activity in SMMC-7721 human hepatoma both in vitro and in nude mice. Its mechanisms might be associated with mitotic arrest, subsequently, apoptosis of the hepatoma cells. No obvious toxicity was observed with in vivo administration of taxol.